Bronchoscopic treatment of a giant bronchopleural fistula with autologous platelet-rich plasma - Shihu Liu; Yunpeng Xuan; Yongjie Wang; Haiyan Wang (Journal of Cardiothoracic Surgery)
Abstract Background Bronchopleural fistula (BPF) is a severe complication observed in patients undergoing lobectomy or pneumonectomy, often resulting in high morbidity and mortality rates. Case presentation We present a case of successful treatment of a giant bronchopleural fistula (20 mm *10 mm). The patient underwent a thoracoscopic right lower lobectomy.The approach we used was local injection of autologous frozen platelet-rich plasma (PRP) with bronchoscopic assistance while maintaining digital chest drainage.We chose the treatment of PRP combined with digital drainage for bronchopleural fistula, not only healing of the fistula but also focusing on elimination of the residual cavity in the thoracic cavity. Conclusion This highlights the effectiveness of this comprehensive approach in the treatment of bronchopleural fistulae and provides a promising treatment option for future treatment of similarly large bronchopleural fistulae.